Embodied empathy: Using affective computing to incarnate human emotion and cognition in architecture. (December 2021) - Ghandi, Mona; Blaisdell, Marcus; Ismail, Mohamed
This research aims to develop a cyber-physical adaptive architectural space capable of real-time responses to people's emotions, based on biological and neurological data. To achieve this goal, we integrated artificial intelligence (AI), wearable technology, sensory environments, and adaptive architecture to create an emotional bond between a space and its occupants and encourage affective emotional interactions between the two. The project's objectives were to (1) measure and analyze biological and neurological data to detect emotions, (2) map and illustrate that emotional data, and (3) link occupants' emotions and cognition to a built environment through a real-time emotive feedback loop. Using an interactive installation as a case study, this work examines the cognition-emotion-space interaction through changes in volume, color, and light as a means of emotional expression. It contributes to the current theory and practice of cyber-physical design and the role AI plays, as well as the interaction of technology and empathy.